2016
DOI: 10.5539/elt.v9n9p139
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus of Writing, Pronunciation, Reading, and Listening by Learners of English as a Foreign Language

Abstract: <p>In order to develop effective teaching methods and computer-assisted language teaching systems for learners of English as a foreign language who need to study the basic linguistic competences for writing, pronunciation, reading, and listening, it is necessary to first investigate which vocabulary and grammar they have or have not yet learned. Identifying such vocabulary and grammar requires a learner corpus for analyzing the accuracy and fluency of learners’ linguistic competences. However, it is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The interpretation of this term in literature is a language research based on examples of language use in real life. Literature [19] holds that corpus linguistics is the starting point of language description or the method of verifying language hypotheses based on a corpus. Reference [20] realizes the mining of candidate parallel texts through cross language information retrieval technology, and users use one language to retrieve the required information from the data set expressed in another or more languages.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…The interpretation of this term in literature is a language research based on examples of language use in real life. Literature [19] holds that corpus linguistics is the starting point of language description or the method of verifying language hypotheses based on a corpus. Reference [20] realizes the mining of candidate parallel texts through cross language information retrieval technology, and users use one language to retrieve the required information from the data set expressed in another or more languages.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…Liu and Han (2015) explained corpora as the combination of a large number of language materials with searching and management software stored in a computer, which could store, classify, retrieve, and deduce common wordings and sentence patterns. Kotani et al (2016) indicated that studentcentered teaching allowed students to apply the language corpus to learn languages, understand the real use of languages better, and organize language models and structures. Redmond and Warren (2014) demonstrated that learners could use the corpus according to their personal demands and find the proper way to use a language, which further proved that teachers were no longer the provider of knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The tasks that were given to the speakers for the spoken data collection varied. Some recorded sentence reading (e.g., Corpus of Writing, Pronunciation, Reading, and Listening by Learners of English as a Foreign Language, Kotani et al, 2016), national spoken English test (the College Learners' Spoken English Corpus, Yang and Wei, 2005), role plays (the Barcelona English Language Corpus, Muñoz, 2006), story description (the Santiago University Learner of English Corpus), and interviews (The Louvain International Database of Spoken English Interlanguage, Gilquin et al, 2010). Some corpora provide transcription of a phonetic level (the LeaP Corpus : Learning Prosody in a Foreign Language, Slavianova, 2007), while some corpora focus on word level transcription (ICNALE: the International Corpus Network of Asian Learners of English, Ishikawa, 2013).…”
Section: Overviewmentioning
confidence: 99%